Analisis Sensitivitas Prioritas Kriteria Pada Metode Analytical Hierarchy Process (Kasus Penentuan Pemberian Kredit) - Wiguna, I Komang Arya Ganda; Semadi, Ketut Ngurah; Sudipa, I Gede Iwan; Septiawan, I Kadek Jerry (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2022)
The criteria affect a priority decision to find out the most important criteria in the Analytical Hierarchy Process (AHP) seen from the priority weights generated by the calculation. However, the analysis of the importance of priorities is to find out how important changes in the weight of the criteria can change the order results of alternative rankings and how critical the alternative values on the criteria are in influencing the ranking results. This study uses an example of providing credit with six criteria, namely Collateral (C1), Business Status (C2), Total Dependents (C3), Loan Amount (C4), Ability to Pay (C5) and Loan Term (C6). The test results from the three processes of sensitivity analysis with changes in the weight of the criteria show criteria C2 with a sensitivity value of 1.13284, Criterion C1 with a sensitivity value of 0.34874 and Criterion C5 with a sensitivity value of 1.078735. The highest percentage of alternative changes shows criteria C2, C4 and C5 with a percentage of 16.67%